STRATEGY FOR DEVELOPING THE STIEIMA SMALL BUSINESS INCUBATOR TO ENHANCE THE COMPETITIVE ADVANTAGE OF STUDENT TENANTS - Hakim, Lukman; Indayani, Lulud Farida; Apriansyah , Raditya Putra; Azhalya, Rafalda Nabalia; Azizatunisa , Rahmatia; Putri , Regina Widya Erisa; P.P, Reva Lina Oktavia; Wolla, Veronika Soneta; Istifania , Yessa Putri; Setyawati , Amelia (Nusantara Economics and Entrepreneurships Journals, 2025)
The STIEIMA Small Business Incubator is a campus facility that serves as a forum for developing student entrepreneurship through training programs, mentoring, and real-world business practices. This study aims to formulate incubator development strategies to enhance the competitive advantage of student tenants through a qualitative descriptive approach and SWOT analysis. Data was collected through observation of incubator operations, interviews with managers and student tenants, and documentation of sales activities and simple financial records. The results show that the incubator has strengths in the form of independent production capabilities and access to low-cost suppliers, but still faces weaknesses such as an unstrategic location, limited facilities, narrow operating hours, and the risk of defective products. Development opportunities lie in the digitization of marketing and the potential for opening online stores, while threats come from business competition around the campus and the increase in online sellers. Based on the SWOT matrix, the recommended development strategies include: optimizing digital marketing to expand the market, improving operational efficiency, diversifying products, and strengthening the management system and quality SOPs. This strategy is expected to increase the competitiveness of student tenants, strengthen the campus entrepreneurship ecosystem, and ensure the sustainability of the incubator as a center for academic-based business development.